The Underutilization, Adverse Reactions and Efficacy of Statins after Liver Transplant: A Meta-Analysis and Systematic Review - Ho, Yeung Jek; Koh, Audrey Su-Min; Ong, Zhi Hao; Ng, Cheng Han; Kong, Gwyneth; Chew, Nicholas W.S.; Lim, Hui Ning; Siddiqui, M. Shadab; Muthiah, Mark Dhinesh (Transplantology (Basel, Switzerland), 2021)
(1) Background: Treatment of dyslipidemia via statin therapy in the non-liver transplant (LT) population is associated with a mortality benefit; however, the impact of statin therapy in post-LT population is not well-defined. This meta-analysis seeks to investigate the safety and efficacy of statin therapy in post-LT patients. (2) Methods: A systematic literature search on Medline and EMBASE database was conducted. A single-arm proportional meta-analysis and conventional pair-wise meta-analysis were performed to compare different outcomes with a random effects model. (3) Results: A total of 11 studies were included in this study, with 697 LT recipients identified to be on statin therapy. Statins were underutilized with only 32% (95% CI: 0.15–0.52) of 1094 post-LT patients on therapy. The incidence of adverse events of 14% (95% CI: 0.05–0.25) related to statin therapy was low. A significant mortality benefit was noted in patients on statin therapy with HR = 0.282 (95% CI: 0.154–0.517, p < 0.001), and improved lipid profiles post LT. The use of statins also significantly decreased odds of graft rejection (OR = 0.33; 95% CI: 0.15–0.73) and hepatocellular carcinoma (HCC) recurrence (HR = 0.32, 95% CI: 0.11–0.89). (4) Conclusions: Statin therapy is safe and efficacious in post-LT patients. Future studies to evaluate the effects of interactions between statins and immunosuppressant therapy are warranted.